Socio-financial functioning of sugarcane (saccharum officinarum l.) processing for the production of panela: the case of the Bellavista village (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2023)
The cultivation of sugarcane for panela production has been an economic and social alternative to diversify farm income. Thus, in the study site, this crop has been grown for more than forty years, and there needs to be clarity on the social and financial aspects of the sugarcane-producing farms, which could account for groups of farms by social and financial arrangement. The paradigm that guided the research was the analytical, empirical one, with a descriptive type of research. As a result, it was obtained that the main determinant of the similarity groups in the sugarcane producers' farms is the production expenses; however, the Ebidta margin has a differential behavior by a social and financial arrangement identified.
Keywords: farmers; economy; panela; production; rurality